Rural Health - Investment, Research and Implications 2023
DOI: 10.5772/intechopen.109885
|View full text |Cite
|
Sign up to set email alerts
|

Perspective Chapter: Integrating Traditional Healers into the National Health Care System – A Review and Reflection

Abstract: This paper reviews and reflects on the policy efforts to integrate traditional healers in Nepal. Most people in rural Nepal rely on traditional healers for their primary health care needs, not only because health facilities in rural areas are poorly functioning but also because these healers meet various health care needs. The kind of traditional medicine provided by traditional healers (such as herbalists, bone setters, faith healers, and traditional midwives) is much more accessible to them than the practiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 16 publications
0
5
1
Order By: Relevance
“…Findings from this study showed that contrary to earlier studies (Subedi 2023, Ampomah et al 2022, traditional medicine practitioners (TMP) and biomedical health workers are generally willing to cooperate in the delivery of health care to the local community members (Solera-Deucher et al 2020, Krah et al 2018. There existed a certain level of formalization and standardization as some members of the Federation of Traditional Medicine Practitioners Association (GHAFTRAM) had identification cards and even referral cards in some few instances allowing them to transfer patients to the biomedical health centers.…”
Section: Integration Of Traditional Medicine Practice Into the Health...contrasting
confidence: 99%
“…Findings from this study showed that contrary to earlier studies (Subedi 2023, Ampomah et al 2022, traditional medicine practitioners (TMP) and biomedical health workers are generally willing to cooperate in the delivery of health care to the local community members (Solera-Deucher et al 2020, Krah et al 2018. There existed a certain level of formalization and standardization as some members of the Federation of Traditional Medicine Practitioners Association (GHAFTRAM) had identification cards and even referral cards in some few instances allowing them to transfer patients to the biomedical health centers.…”
Section: Integration Of Traditional Medicine Practice Into the Health...contrasting
confidence: 99%
“…Likewise, Articles 24 and 31 encourage them to maintain, control, protect and develop their traditional medicine, health practices and cultural expressions (8). This is supported by recommendations that trained and categorised healers with recognised competencies should be identified, profiled, registered, monitored and evaluated and get certified by accredited institution that understand, contextualize, appreciate, and recognise them and their practices (14,15). More authors argue that this would assist to harmonise, streamline, regulate and promote informal skills development, qualifications, and accreditation of their practices, therapies, and services (16)(17)(18)(19).…”
Section: Introductionmentioning
confidence: 99%
“…They are challenged by lack of legal status, which aspect sustains their experience of unfavourable direct and indirect foreign rule (44). Therefore, training and practice engaging ancestral spirits during health management is vulnerable to widespread charlatanism, misinformation, ambiguity (13,45), and no official levels of utilization of traditional spiritual healers in health care (15). It is, therefore, a national challenge and priority to understand and regulate training of traditional spiritual healers, their practices and premises (43) so as to inform policy (23).…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, Articles 24 and 31 encourage them to maintain, control, protect and develop their traditional medicine, health practices and cultural expressions [ 8 ]. This is supported by recommendations that trained and categorised healers with recognised competencies should be identified, profiled, registered, monitored and evaluated and get certified by accredited institution that understand, contextualize, appreciate, and recognise them and their practices [ 14 , 15 ]. More authors argue that this would assist to harmonise, streamline, regulate and promote informal skills development, qualifications, and accreditation of their practices, therapies, and services [ 16 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…They are challenged by lack of legal status, which aspect sustains their experience of unfavourable direct and indirect foreign rule [ 39 ]. Therefore, training and practice engaging ancestral spirits during health management is vulnerable to widespread charlatanism, misinformation, ambiguity [ 13 , 40 ], and no official levels of utilization of traditional spiritual healers in health care [ 15 ]. It is, therefore, a national challenge and priority to understand and regulate training of traditional spiritual healers, their practices and premises [ 38 ] so as to inform policy [ 23 ].…”
Section: Introductionmentioning
confidence: 99%